A new pushover procedure for estimating seismic demand of double-layer barrel vault roof with vertical double-layer walls. (December 2021) - Kheirollahi, Mohammad; Abedi, Karim; Chenaghlou, Mohammad Reza
Abstract: Recent investigations indicate that pushover methods have been widely applied for the seismic evaluation of common structures, whereas a limited number of researches have been conducted for the pushover analyses of space structures. In this study, a new and an appropriate approach, named the Dynamic Load Pattern-Based Pushover Analysis (DLP-PA), has been proposed for predicting the seismic demands of walled double-layer barrel vault roofs, referred to herein as DLRWs. In this method, invariant lateral and vertical force distributions are obtained by averaging the level forces from linear time history analyses of the space structures for a set of ground motions. In this procedure, the seismic demands are finally obtained by enveloping the results of conventional first-mode and the DLP-PA approaches. Numerical models with different geometric properties have been employed to study the efficiency of the proposed analysis method. The responses of models, using the proposed pushover analysis, are compared with incremental dynamic analysis (IDA) results. Also, the responses have been compared with those of the modal pushover analysis (MPA), extended N2 (EN2), modified consecutive modal pushover (MCMP), a single-analysis multi-mode pushover (SMP) and non-adaptive displacement-based pushover (NADP) procedures. The obtained results demonstrate that DLP-PA approach provide good estimation of seismic demand parameters.